1999
DOI: 10.1038/sj.bjc.6690346
|View full text |Cite
|
Sign up to set email alerts
|

Promoting patient participation in the cancer consultation: evaluation of a prompt sheet and coaching in question-asking

Abstract: Summary Active participation in the medical consultation has been demonstrated to benefit aspects of patients' subsequent psychological well-being. We investigated two interventions promoting patient question-asking behaviour. The first was a question prompt sheet provided before the consultation, which was endorsed and worked through by the clinician. The second was a face to face coaching session exploring the benefits of, and barriers to, question-asking, followed by coaching in question-asking behaviour em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
192
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(196 citation statements)
references
References 23 publications
2
192
1
1
Order By: Relevance
“…Roter initiated this line of research into question-asking and found in a randomized controlled trial that patients coached to make a personalized list of questions before a primary care consultation asked more direct questions during the visit [2]. Others found similar results, even when prompt sheets were used without coaching [4][5][6][7]. Overall, a meta-analysis of question-listing interventions featuring 8,244 patients in 33 randomized controlled trials found an increase in questionasking [8].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Roter initiated this line of research into question-asking and found in a randomized controlled trial that patients coached to make a personalized list of questions before a primary care consultation asked more direct questions during the visit [2]. Others found similar results, even when prompt sheets were used without coaching [4][5][6][7]. Overall, a meta-analysis of question-listing interventions featuring 8,244 patients in 33 randomized controlled trials found an increase in questionasking [8].…”
Section: Introductionmentioning
confidence: 85%
“…After extensive work in academic settings [5][6][7]9, 10], Dimoska et al published an account of a limited-term implementation in a community clinic in Australia [11]. Belkora and colleagues have reported on long-term implementations in academic and community settings with a regional reach around Northern California [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Newly referred counselees may be helped by receiving more information on the counselling procedure prior to the consultation, and they may be advised on how to prepare their visit. They may, for example, be encouraged to write down questions in advance, possibly helped by a prompt sheet such as was successfully devised for promoting cancer patients' participation (Brown et al, 1999;Wells et al, 2004), or to send questions ahead to the counsellor.…”
Section: Resultsmentioning
confidence: 99%
“…We developed and tested a question prompt list designed to improve communication when cancer patients see a medical or radiation oncologist for the first time. In three separate randomised trials of this intervention, prognosis was the only topic about which patients who received the question prompt list asked more questions, even though only two of the 17 suggested questions were about prognosis (Butow et al, 1994;Brown et al, 1999Brown et al, , 2001. This failure to discuss prognosis is probably caused as much by doctors' uncertainty about how to think and talk about prognosis as it is by patients' reluctance to ask about it (Brown et al, 1999(Brown et al, , 2001).…”
mentioning
confidence: 99%
“…In three separate randomised trials of this intervention, prognosis was the only topic about which patients who received the question prompt list asked more questions, even though only two of the 17 suggested questions were about prognosis (Butow et al, 1994;Brown et al, 1999Brown et al, , 2001. This failure to discuss prognosis is probably caused as much by doctors' uncertainty about how to think and talk about prognosis as it is by patients' reluctance to ask about it (Brown et al, 1999(Brown et al, , 2001). Christakis and Lamont (2000) reported that doctors were inaccurate in their estimates of prognosis for terminally ill patients, and that their errors were systematically optimistic.…”
mentioning
confidence: 99%